Sequential left ventricular electro-mechanical changes in left bundle branch pacing vs right ventricular pacing a two-center study. (3rd October 2022) - Mao, Y K; Yang, Y; Duchenne, J; Garweg, C; Sheng, X; Zhang, J F; Yang, Y E; Wang, M; Yang, Y; Voros, G; Sun, Y X; Ma, M M; et al.
Abstract: Background: Left bundle branch pacing (LBBP) has been proved to maintain electrical synchrony better than RVP during mid to long-term follow-up, but little is known about the left ventricular (LV) mechanical changes over time. This study investigates if LBBP causes less sequential electro-mechanical alterations in LV that develop over time, compared with both conventional (CRVP) and leadless (LRVP) RVP. Methods: Sixty-five patients with pacing indication for bradycardia were prospectively enrolled: Twenty-two were treated with LBBP, 23 with CRVP and 20 with LRVP. QRS duration (QRSd) was measured at baseline and during follow-up. All patients underwent echocardiography at baseline, one week after implantation and at one-year follow-up. LV volumes, ejection fraction (EF) and global longitudinal strain (GLS) were measured. Septal flash (SF), apical rocking and septal longitudinal strain patterns were assessed visually by two experienced readers. Results: All the patients presented with normal strain pattern and no signs of SF or apical rocking at baseline. 100% of CRVP and 95% of LRVP patients had stage1 or 2 septal deformation patterns at week 1, and the majority (72.3% CRVP and 83.3% LRVP) progressed to stage≥2 at 12 months. On the contrary, over 2/3 of LBBP patients preserved normal strain patterns at week 1, and less than 1/3 had stage-1 pattern, 2 out of whom progressed to stage-2 during follow-up (Figure 1). At week 1 and 12 months, all RVP patients had SF, and most of them also exhibited apical rocking (87%-94.4% in CRVP and 80%-94.4% in LRVP). However, much less septal flash and apical rocking was induced in LBBP patients at week 1 and last follow-up (27.3%-37.5% and 22.7%-25%, P<0.001 vs RVP). Baseline QRSd were similar among three groups. At week 1, the paced QRSd increased least in LBBP compared to CRVP and LRVP and remained as such at 12 months. During one year follow-up, LVEF and LV GLS decreased more in CRVP group compared to LBBP (both P<0.05) (Figure 2). Conclusion: LBBP causes less sequential changes in LV deformation patterns, septal flash and apical rocking, compared to CRVP and LRVP. With this, LBBP appears to preserve LV function better than RVP. CRVP and LRVP did not differ in electro-mechanical changes or LV remodeling. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Research Foundation Flanders (FWO) project grant